A case report of pulmonary vein isolation performed in a patient with polysplenia and interrupted inferior vena cava. Issue 12 (30th November 2021) - Kupics, Kaspars; Jubele, Kristine; Nesterovics, Georgijs; Erglis, Andrejs
Abstract: Background: Pulmonary vein isolation (PVI) has entrenched itself as one of the main approaches for the treatment of paroxysmal symptomatic atrial fibrillation (AF). Pulmonary vein isolation prevents focal triggers from pulmonary veins from initiating AF paroxysms. As standard—PVI is performed through the inferior vena cava (IVC) approach, through the femoral vein. However, there are conditions when this approach is not appropriate or is not available. Case summary: We report a case of a 53-year-old male who was referred to Pauls Stradins Clinical University Hospital for PVI due to worsening AF. Due to the rare anatomical variant of the venous system, the standard approach to PVI could not be applied. Interrupted cava inferior did not allow for femoral vein and IVC access. We had to figure out a different path—a combination of internal jugular and subclavian veins was used. Transseptal puncture was performed under transoesophageal echocardiography (TOE) control with a puncture needle stiletto. Pulmonary veins were isolated successfully, no complications were observed, and the patient was discharged in sinus rhythm. Discussion: In some patients, PVI cannot be done through the standard IVC approach. In such cases, a different venous access must be chosen. Our patient had a rare variant of interrupted IVC and we had to use superior vena cava approach for the procedure. The difficulty of this approach is that procedure instruments are not designed for non-standard venous access; however, a combined use of TOE, general anaesthesia, and contact force-guided ablation has succeeded in isolating patients' pulmonary veins.